2012
DOI: 10.1108/00012531211244716
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the network structure of science parks

Abstract: Purpose -This study introduces a method based on link analysis to investigate the structure of the R&D support infrastructure associated with science parks in order to determine whether this webometric approach gives plausible results. Design/Methodology/Approach -Three science parks from Yorkshire and the Humber in the UK were analysed with webometric and social network analysis techniques. Interlinking networks were generated through the combination of two different data sets extracted from three sources (Ya… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Finally, there is a search for alternative methodological approaches and indicators in the studies of networks of university-industry relations. Some authors propose the use of webometric approaches (Kim, 2012;Minguillo & Thelwall, 2012) and other authors propose the use of simultaneous indicators of relational characteristics, such as citations, project participation, questionnaires or other data (Almodovar & Teixeira, 2014;Furukawa, Shirakawa, & Okuwada, 2011;Heimeriks et al, 2003), arguing that analysis based on a single indicator underestimate the level and may not capture all of the complexities of the collaboration patterns.…”
Section: Methodological Contributionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, there is a search for alternative methodological approaches and indicators in the studies of networks of university-industry relations. Some authors propose the use of webometric approaches (Kim, 2012;Minguillo & Thelwall, 2012) and other authors propose the use of simultaneous indicators of relational characteristics, such as citations, project participation, questionnaires or other data (Almodovar & Teixeira, 2014;Furukawa, Shirakawa, & Okuwada, 2011;Heimeriks et al, 2003), arguing that analysis based on a single indicator underestimate the level and may not capture all of the complexities of the collaboration patterns.…”
Section: Methodological Contributionsmentioning
confidence: 99%
“…Public research organizations as central actors in innovation networks (Breschi & Catalini, 2010;De Stefano & Zaccarin, 2013;Lissoni, 2010;Minguillo & Thelwall, 2012;Protogerou et al, 2013) • Academic authors-inventors assume more brokerage positions.…”
Section: Strong and Weak Ties And Structural Holesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the international literature has shown that many experiences with technology parks failed to achieve the expected results (European Commission, 2007;Gaino and Pamplona, 2012). In this sense, some researchers suggest that future studies should address the assessment of research and development networks (where technology parks are located) and develop ways to identify the interactions that may be relevant for innovation in technology park environments (Chen and Huang, 2004;Minguillo and Thelwall, 2012). Some authors recommend new studies to address innovative assessments and practices regarding the operation of technology parks, to help park-based companies develop more efficient and effective forms of work and results (Gkypali et al, 2016;Yan and Chien, 2013).…”
Section: Introductionmentioning
confidence: 99%